The Jurisprudential Maxim (Translator’s Statement is Absolutely Accepted) Between Islamic Law and Civil Procedures Law in the Sultanate of Oman And Contemporary Applications - Al-Fahdi, Fahad Khamis Ahmad (Arab Journal for Sciences and Research Publishing, 2020)
This research aims at clarifying the significance of and studying and establishing the jurisprudential maxims, especially those related to the judiciary so that they help judges in their work, muftis in their understanding and students in their memorization. The maxim of (Translator’s Statement is Absolutely Accepted) is a great maxim since it represents a principle in the judicial ruling. This research is a new addition to the comparative jurisprudential literature, an approach between Islamic jurisprudence and contemporary law, and a manifestation of the greatness of Islamic Sharia that cares for all aspects of life. This research is divided into two subjects: First: the definition of terms such as maxim, jurisprudence and law in three sections. Second: the explanation and establishment of the maxim and the legal status in four sections, as well as the judicial applications. The researcher concludes the study with the most important results, that of the jurisprudential maxims combine different issues in simple eloquent phrases, and that the procedures law has noble Sharia purposes, represented in caring for the interests of people and achieving the highest meanings of integrity and justice. The Islamic jurisprudence pays attention to the maxims of the rules of procedures more than the positive laws do. The law considers the Islamic Jurisprudence regarding the translator issue, unless in oath-taking. Translators shall be fair, familiar with both languages, and accepts a single statement. Among the most important recommendations: the provisions of jurisprudential maxims shall be contained in bills, and the judges shall consider the maxim in all filed cases. In addition, education courses should be held for translators so that they know the procedures of the progress of cases in courts, and the criticality of accuracy.
Keywords: Legal Principle; Procedural Law; Civil and Commercial Procedures Law; Sultanate of Oman; Islamic Jurisprudence